La sfida al labirinto sessuale. L’eros nell’opera di Italo Calvino - Baldi, Elio (Incontri. Rivista europea di studi italiani, 2012)
The Challenge of the Sexual Labyrinth Sensuality in the Work of Italo CalvinoIn this article, the novels, stories and essays of Italo Calvino are being studied from the perspective of sensuality and Eros. In literary criticism Calvino’s work is rarely being associated with sexuality, even though the subject did fuel the imagination of the writer himself. Calvino recognized the importance of the theme of sexuality in literature as well as the challenge inherent in trying to depict faithfully a similar ineffable subject, that has, moreover, been covered by society under a thick layer of clichés and repetitive language and therefore been emptied of meaning. The importance of a non-banal, renewing sexuality in literature inspired Calvino to experiment in a light, humorous, surprising way with a myriad of forms of literary sensuality. Calvino has searched Eros in space, as the prime mover in evolution, amongst animals and celestial bodies (instead of the usual heavenly bodies), in rituals and objects, in the heads of his characters, but seldom there where the reader would expect it to be. In a mild and often indirect way Calvino integrates his reflections on the subject in his short stories and comments on the role of sexuality in modern society and literature.